Fiscal equalization and the tax structure - Fédéric Holm-Hadulla (European Central Bank (ECB), 2018)
Sub-national governments often finance substantial parts of their budgets via taxes on capital or other mobile factors - despite having access to alternative, less distortionary, revenue sources. This paper develops three hypotheses to explain this pattern and tests them in a natural experiment from Germany. The first hypothesis is that fiscal redistribution between jurisdictions lowers the perceived excess burden of distortionary taxation and thereby raises its attractiveness from the perspective of local governments; the second is that a desire for redistribution within jurisdictions induces a shift away from less distortionary tax instruments, despite their superior efficiency properties; the third is that distortionary taxation serves as a Pigouvian intervention to correct externalities. The empirical analysis supports redistribution between jurisdictions as important, but insufficient, to fully explain the observed reliance on distortionary taxation. Among the remaining two hypotheses, the data favour Pigouvian over distributional motives as a further rationale for the local taxation of mobile factors.
Keywords: H23; H25; H71; H77; 330; Federalism; Fiscal Equalization; Tax Structure; Natural Experiment; Differencein-Difference